Standardization of pre-sowing seed treatment with selected biofertilizers and different packaging materials on seedling parameters of sorghum (Sorghum bicolor L.) during storage - Tirthajyoti Roy; Prashant Kumar Rai; Shivam Kumar Rai (Annals of Agricultural Research, 2024)
A laboratory experiment was carried out at the Seed Testing Laboratory of the Department of Genetics and Plant Breeding, Sam Higginbottom Institute of Agriculture Technology and Science in Prayagraj, Uttar Pradesh during the kharif season of 2023. The study aimed to assess the quality of sorghum (Sorghum bicolor L.) variety Nutra seeds and evaluate the effectiveness of various biofertilizers as pre-sowing seed treatments on the seedling parameters of sorghum under ambient storage conditions. For a three-month period, sorghum seeds were stored in the laboratory using cloth bags and aluminum foil pouches at ambient temperatures. The experimental design employed a completely randomized setup with four replications. The seeds were subjected to different treatments, including Trichoderma viride @ 10% and 15% conc. for 12 hours, Pseudomo nas fluorescens @ 10% and 15% conc. for 12 hours, VAM @ 10% and 15% conc. for 12 hours, Azospirillum @ 10% and 15% conc. for 12 hours, Azotobacter @ 10% and 15% conc. for 12 hours, Rhizobium @ 10% and 15% conc. for 12 hours. This allowed for the observation of the impact of various biopriming techniques and packaging materials (aluminum foil pouches and cloth bags) on the seed quality of stored sorghum. Among the treatments, the maximum seed germination percentage (86.6%), fresh weight (2.09 g), dry weight (0.472 g), root length (13.2cm), shoot length (13.7 cm), seedling length (28.04 cm), vigour index-I (2429.8), and vigour index-II (40.85) were recorded for the seeds treated with Pseudomonas fluorescens at 15% conc. for 12 hoursafter 3 months storage period whereas lowest result found in control. The choice of packaging materi als also exerted a significant influence on seedling growth parameters. Seeds stored in aluminum foil pouches showed the best performance after three months of storage, while the lowest was observed in the cloth bag. In conclusion, the study highlights the positive impact of Pseudomonas fluorescens at 15% concentration for 12 hours as an effective biopriming treatment for enhancing sorghum seed quality under ambient storage conditions. Additionally, the choice of packaging material, with aluminum foil pouches demonstrating su perior results, underscores the importance of proper storage practices in maintaining seedling parameters during storage.